(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Listeria monocytogenes (L. monocytogenes) is a Gram-positive, facultative intracellular bacterial pathogen that can cause a severe invasive disease (listeriosis) mainly in pregnant women. Based on genetic content, L. monocytogenes can be divided into 3 lineages I, II and III. Several molecular methods have been developed to assist in the characterization of L. monocytogenes, macrorestriction analysis by pulse-field gel electrophoresis (PFGE) is one of the most used methods for the genotyping of L. monocytogenes. Objective: To determine the predominant genotype of L. monocytogenes isolated from clinical cases in a group of aborted Iraqi women. Methods: A study was designed and included 15 clinical isolates of L. monocytogenes and one isolate from locally made cheese. The PFGE protocol was performed as described by Graves and Swaminathan. Briefly, bacterial suspensions adjusted to optical density of 1.3 at 610 nm were embedded in 1.2% Sea Kem Gold agarose plugs. The lysed, washed five times and a 2 mm thick piece was cut, equilibrated and digested with 200 ?l of AscI enzyme master mix at 37 °C for 2 h. The macrorestriction fragments were separated by electrophoresis on a CHEF-DRIIBIO-RAD. Images were analyzed with the software Bio Numerics Gel Compar II version 6.6.11 (Applied Maths). Results: All L. monocytogenes isolates displayed AscI digestion profiles after incubation with the enzyme, about 6-12 majorfragments of 30 to 675 kb were obtained, sixteen isolates have been used in this study, however, 11 different AscI profiles were encountered, the distribution of the isolates according to the restriction profiles showed that two profiles were the most predominant A, A2 with a percentage of similarity of 100%. Conclusion: L. monocytogenes genotyping showed profiles that can be well used in tracing down infection source and outbreak of this bacterium. PFGE represents a great discrimination and reproducibility method for molecular sub-typing of L. monocytogenes and it is considered the gold standard. Keywords: Listeria monocytogenes, genotyping, placenta, aborted women, pulse field gel electrophoresis Citation: Qassim KW, AL Attraqchi AAF, Khatab YI. Genotyping of Listeria Monocytogenes in Iraqi women with spontaneous abortion using pulse field gel electrophoresis. Iraqi JMS. 2018; Vol. 16(1): 8-13. doi: 10.22578/IJMS.16.1.3